Optimizing the Osanna Beach Resort Website as a Digital Foundation to Enhance Promotional through Digital Marketing - Dwi Ariani Finda Yuniarti; Agus Prianggono; Anwar Fu’adi; Bagus Hikmahwan; Fajar Abadi (STKIP Singkawang, 2025)
Osanna Beach Resort, one of the most tourist destinations in Pacitan Regency, does not yet have an official website. This condition results in the resort lacking a strong digital foundation to support sustainable marketing efforts. This Community Service Program (PKM) activity aims to develop the official Osanna Beach Resort website as a digital promotional medium. The implementation method uses a participatory approach combined with WDLC, through the stages of needs analysis, design, implementation with CMS WordPress, testing, launch, maintenance, socialization, and content management training for resort managers. The implementation results show that the website www.osannabeach.com has met partners' needs in providing destination information, facilities, reservations, and integration with social media. The questionnaire analysis of six assessment indicators obtained an average score of 95.35%, with details of color (98.69%), typography (95.74%), layout (90.49%), image quality (97.05%), ease of navigation (97.05%), and user comfort (93.11%). These findings confirm that the developed website design is able to provide a good user experience while enhancing the resort's professional image.Optimalisasi Website Osanna Beach Resort sebagai Fondasi Digital untuk Meningkatkan Promosi melalui Digital MarketingABSTRAKOsanna Beach Resort yang merupakan destinasi unggulan di Kabupaten Pacitan tidak memiliki website resmi, sehingga hal ini menyebabkan Osanna Beach Resort belum memiliki pondasi digital yang kuat untuk mendukung pemasaran berkelanjutan. Kegiatan PKM ini bertujuan untuk mengembangkan website resmi Osanna Beach Resort sebagai media promosi digital. Metode pelaksanaan menggunakan pendekatan partisipatif yang dipadukan dengan WDLC, melalui tahapan analisis kebutuhan, perancangan desain, implementasi dengan CMS WordPress, pengujian, peluncuran, pemeliharaan serta sosialisasi dan pelatihan pengelolaan konten kepada pengelola resort. Hasil implementasi menunjukkan bahwa website www.osannabeach.com telah memenuhi kebutuhan mitra dalam menyediakan informasi destinasi, fasilitas, reservasi dan integrasi dengan media sosial. Analisis kuesioner terhadap 6 indikaotr penilaian memperoleh rata-rata 95,35% dengan rincian aspek warna (98,69%), tipografi (95,74%), tata letak (90,49%), kualitas gambar (97,05%), kemudahan navigasi (97,05%) dan kenyamanan pengguna (93,11%). Temuan ini menegaskan bahwa desain website yang dikembangkan mampu memberikan pengalaman pengguna yang baik sekaligus meningkatkan citra profesional resort.Kata Kunci:pariwisata; digital marketing; website; WDLC; Osanna Beach Resort